POLITIK HUKUM PERUBAHAN MASA JABATAN KEPALA DESA DI INDONESIA - Nurudin, Nurudin; Hamdi, Muh. Rizal (PRODI HUKUM TATANEGARA, 2024)
The aim of this research is to explain the political and legal aspects of changes in the terms of office of village heads in Indonesia and to analyze the maslahah perspective. This research is a descriptive-analytic literature study using a normative approach. The results of this research are that the current term of office and period of the village head is considered insufficient to develop the village due to the tension and polarization of society after the Village Head Election, the village head's term of office being too short will result in failure to achieve the vision and mission. However, this cannot be used as an absolute reason for extending the term of office of the village head, considering that it will be the entry point for changes to be made in aspects of the terms of the executive institutions of the president, governor, regent, mayor and legislative institutions, both the DPR and DPD at the center and also in the area. The extension of the term of office at the village government level has the potential to make the democratic climate of village government unhealthy and can even foster oligarchy in the village. Giving a village head a long term of office is not a guarantee that a development climate will be developed, the village head is actually required or given a challenge to work effectively and efficiently within the specified period in developing the design of his village. In the perspective of maslahah murlah, namely establishing laws in matters that are not mentioned at all in the Qur'an or al-Sunnah, with consideration for the benefit or interests of human life which is based on the principle of attracting benefits and avoiding damage. The extension of the village head's term of office is actually contrary to the concept of maslahah murlah.